2016
DOI: 10.1007/s11356-016-6203-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and element concentrations in lichens exposed to airborne pollutants released during cement production

Abstract: The content of selected elements (Al, As, Ca, Cd, Cr, Cu, Fe, Hg, Mn, Ni, Pb, S, Ti, V and Zn) was measured in samples of the lichen Evernia prunastri exposed for 30, 90 and 180 days around a cement mill, limestone and basalt quarries and urban and agricultural areas in SW Slovakia. Lichens transplanted around the investigated quarries and the cement mill rapidly (30 days) reflected the deposition of dust-associated elements, namely Ca (at the cement mill and the limestone quarry) and Fe, Ti and V (around the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…Therefore, calcium is coming from an environmental source, probably as calcite particles that deposit on the lichen surface and are incorporated to the metabolism. The discussion on the atmospheric intake of calcite particles by diverse lichen genera is not a novelty, [14,34] but in the authors' knowledge, the distribution of the biominerals related with this process on the lichen-support interface has not been described up to now by means of Raman spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, calcium is coming from an environmental source, probably as calcite particles that deposit on the lichen surface and are incorporated to the metabolism. The discussion on the atmospheric intake of calcite particles by diverse lichen genera is not a novelty, [14,34] but in the authors' knowledge, the distribution of the biominerals related with this process on the lichen-support interface has not been described up to now by means of Raman spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Transplants of the same lichen species exposed for 2 months in an industrial area showed values in the range 0.4 to 7.4 × 10 −8 m 3 /kg −1 [46]. Transplants of Evernia prunastri exposed for 6 months around a cement production plant in Slovakia showed magnetic susceptibility ranging 1.3 to 8.1 × 10 −8 m 3 /kg −1 [47]. Bags of Parmotrema pilosum exposed to atmospheric pollutants over the course of 1 year increased from an initial mass-specific magnetic susceptibility value (mean ± S.D.)…”
Section: Discussionmentioning
confidence: 98%
“…Magnetic properties have been reported recently of terrestrial mosses and lichens 116,136,137 and moss bags 41,127,135,[138][139][140][141] . Because of their high accumulation capacity and high surface:volume ratio, mosses and lichens are suitable for magnetic evaluation of environmental pollution 116 .…”
Section: Magnetic Signatures Of Mosses and Lichensmentioning
confidence: 98%